Rencana Penerapan Ganjil Genap di Kota Bandung - Damara, Devlin; Rachmat, Shanty Yulianti (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
The high use of private vehicles in big cities, including the city of Bandung, also increases negative impacts, one of which is congestion. For this reason, it is necessary to limit private vehicles so that negative impacts can be reduced. One of them is by carrying out odd-even trials in the city of Bandung, to determine the impact on transportation conditions. Literature studies show that odd-even can reduce travel time, reduce vehicle volume, increase vehicle speed, and reduce pollution levels. Some countries that have implemented odd-even have felt a positive impact, but there are also those who have felt the opposite. Referring to the success of several cities, including the city of Jakarta, odd-even will also be tested on several roads in the study area. This research aims to determine the percentage of people’s mode choices and changes in road network performance when odd-even is implemented. The method in this research is quantitative based on questionnaires from people who actively pass through the road sections affected by the trial. The results show that people still tend to use private vehicles compared to public transportation. Apart from that, there were visible changes in road performance, where there was a decrease in vehicle volume by 30% and a decrease in travel time of around 17-25 seconds per section on the road tested. Key words: TDM, Odd Even, Transportation